Dengue: una enfermedad reemergente en el departamento del Cusco, Perú. - Atamari Anahui, Noé (2015)
Dengue is an infectious disease caused by a systemic Flavovirus which is transmitted by mosquitoes of the genus Aedes aegypti and albopictus species (1). The incidence of dengue in the Americas in recent years has increased and spread in several countries, being mostly affected the tropical and subtropical regions, with an increase of the disease in urban and suburban areas, thus constituting a major public health problem, especially in developing countries (1). In Peru, in the departments of Loreto, Madre de Dios, Tumbes Cajamarca, Cusco, Lambayeque, Huanuco, La Libertad and Puno in the last year the highest number of confirmed cases was reported and increased outbreaks of dengue in the country (2 ).